Prospective studies are needed of the neurology and neuropsychiatry of COVID-19: reply - Badenoch, James; Watson, Cameron; Cross, Benjamin; Nicholson, Timothy; Rooney, Alasdair (Acta Biomedica Atenei Parmensis, 2020)
N/A